Pendekatan adaptive reuse terhadap perubahan pada karakter visual bangunan konservasi - Amalia Devitasari; Atik Suprapti; Bangun I. R. Harsritanto (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2021)
Semarang Gallery resulted from a heritage building conservation project reused with a new function or known as adaptive reuse, which indicates that it can cause changes in its visual character. This study aims to find the level of change in the visual character of the exterior, interior, and at close range of Semarang Gallery due to the adaptive reuse approach. This research uses a qualitative method, with graphical and descriptive data analysis. The results of the analysis show that the adaptive reuse approach changes the existing building typology, which requires adapting to technical improvements in almost all aspects of the building; thus giving rise to changes in the visual character of the exterior, interior, and at close range with different levels of significance. Changes that are in line with conservation principles can increase its parameter function’s value, on the contrary; inconsistencies can remove the distinctiveness of the visual character.